2013
DOI: 10.5588/ijtld.13.0315
|View full text |Cite
|
Sign up to set email alerts
|

Improving tuberculosis screening and isoniazid preventive therapy in an HIV clinic in Addis Ababa, Ethiopia

Abstract: Summary Setting An HIV clinic in Addis Ababa, Ethiopia. Objective The World Health Organization (WHO) recommends active tuberculosis (TB) case finding among people living with HIV (PLHIV) in resource-limited settings using a symptom-based algorithm and those without active TB disease should be offered isoniazid preventive therapy (IPT). We evaluated rates of adherence to these recommendations and the impact of a quality improvement (QI) intervention. Design A prospective study design was utilized to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…A study in South Africa also reported lack of awareness on the benefits of IPT and the guidelines and recommendations by prescribers as primary barrier to IPT implementation [17]. Provision of a clear up-to-date policy and provision of trainings has been found to improve IPT implementation in other studies [2527]. Trainings and good communication are vital for proper understanding of the policy and avoid ambiguities on IPT provision among health providers.…”
Section: Discussionmentioning
confidence: 99%
“…A study in South Africa also reported lack of awareness on the benefits of IPT and the guidelines and recommendations by prescribers as primary barrier to IPT implementation [17]. Provision of a clear up-to-date policy and provision of trainings has been found to improve IPT implementation in other studies [2527]. Trainings and good communication are vital for proper understanding of the policy and avoid ambiguities on IPT provision among health providers.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach has been implemented in screening for pulmonary TB among HIV-infected persons in RLS, where the absence of four symptoms has been found to have a high NPV for disease and thus abdicates the need for further workup. 20,21 We chose symptoms and signs that are characteristic of CM and readily attainable by clinicians. Although the specificity and PPV were low, the absence of fever (reported or documented), neck stiffness, headache, and meningismus had a 98% NPV for cryptococcemia and 100% for CM.…”
Section: Discussionmentioning
confidence: 99%
“…The non-completion rate of 11%, although on the lower end of the spectrum, is similar to other settings. 22 Most of the sociode- …”
Section: Public Health Actionmentioning
confidence: 99%